2012
DOI: 10.1111/j.1751-0813.2011.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Final‐year student and employer views of essential personal, interpersonal and professional attributes for new veterinary science graduates

Abstract: Final-year students and employers of new graduates from The University of Queensland ascribe similar importance to a variety of personal, interpersonal and professional attributes for new veterinary science graduates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
3
24
3
Order By: Relevance
“…While our findings conflict with what has been previously reported, the importance of graduate self-confidence may be industry-specific, or alternatively it could be that our results indicate a recent shift in employer attitudes towards this attribute. Employers' low ranking of an ability to work in teams and an understanding of ethical conduct is surprising, especially given the corresponding high levels of agreement that these skills and attributes are important, and the broad recognition of teamwork as a desirable graduate attribute (Business Council of Australia, 2011;Casner-Lotto & Barrington, 2006;Schull et al, 2012). The discordance between our results and those observed elsewhere provides a potential opportunity for further investigation.…”
Section: Interpersonal Attributescontrasting
confidence: 50%
“…While our findings conflict with what has been previously reported, the importance of graduate self-confidence may be industry-specific, or alternatively it could be that our results indicate a recent shift in employer attitudes towards this attribute. Employers' low ranking of an ability to work in teams and an understanding of ethical conduct is surprising, especially given the corresponding high levels of agreement that these skills and attributes are important, and the broad recognition of teamwork as a desirable graduate attribute (Business Council of Australia, 2011;Casner-Lotto & Barrington, 2006;Schull et al, 2012). The discordance between our results and those observed elsewhere provides a potential opportunity for further investigation.…”
Section: Interpersonal Attributescontrasting
confidence: 50%
“…The present study replicates previous findings that training in communication and social support skills for grieving clients has been lacking in veterinary training, with the majority of veterinarians indicating their skills for dealing with grieving clients were self‐taught. Previous research has demonstrated that veterinarians agree that good communication is essential to a successful veterinary practice and should be taught as part of the formal veterinary curriculum . Thus, modules in curricula that address the grief and loss of companion animal owners and where to refer them to when they need assistance would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Survey items around 'awareness of limitations' were collectively ranked more important than similar items around reflection, self-audit or acceptance of criticism, including when compared directly within a study Schull et al 2012). Items allocated to 'relationship-centred care' were diverse and suggested an internal split between highly-ranked items around 'gain respect and confidence of clients', and more lowly-ranked personality items such as friendliness, cheerful disposition, good sense of humour, likeable or outgoing personality Schull et al 2012). Research skills were ranked as clearly least important by this meta-analysis; although some caution is required due to the low quantity of evidence (four items from three surveys), this bottom-most ranking was replicated independently by all three studies, across a range of stakeholder groups.…”
Section: Stakeholder Perceptionsmentioning
confidence: 99%